Linking photosynthesis and yield reveals a strategy to improve light use efficiency in a climbing bean breeding population - Keller, Beat (Journal of experimental botany, 2024)
© The Author(s) 2023. Published by Oxford University Press on behalf of the Society for Experimental Biology.